ANATOMI SUATU PERJANJIAN - Edi Krisharyanto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Official or non official document should be sorted into certain parts in order to avoid any misinterpretation of the contents; the sorting activity like an anatomy of human body.